Memperkuat Generasi Religius : Pendampingan Pengajian Jum’at Rutin oleh Siswi – siswi SMK Karsa Mulya Palangka Raya - Ervina Nur Khasanah; Syahmidi Syahmidi; Aniskenia Aniskenia (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the assistance of Routine Friday Recitation at SMK Karsa Mulya Palangka Raya as an effort to strengthen the religious generation. This study uses the participatory action research (PAR) method to involve students in the program development process. The results of the study show that the Routine Friday Recitation program not only produces a skilled generation, but also a religious generation. Students of SMK Karsa Mulya Palangka Raya actively participate in recitation, read the Qur'an, and present religious materials. This program is expected to strengthen students' spiritual foundation, improve public speaking skills, and instill strong moral values.